EFFECTS OF SOCIAL ISOLATION DURING THE COVID-19 PANDEMIC: analysis of domestic violence cases - Silva, Karolayne Brito (2021)
Objective: To analyze, from a literature review, the increase in cases of femicide in the context of the covid-19 pandemic. Methods: Bibliographic study of the integrative literature review type, with a qualitative approach, which took place in the Virtual Health Library databases, coordinated by the Regional Medicine Library (BIREME) and composed of databases such as: Latin American Literature and the Caribbean in Health Sciences (LILACS) and PubMed from the National Library of Medicine. Result: 12 complete publications were selected to support results and conclusion, only publications available in their entirety were included, published in the years 2020 to 2021, in Portuguese, English and Spanish. The included studies highlighted that most of the aggressions are perpetrated by the victims' spouse or ex-partners, as a result, the domestic space in social isolation is undoubtedly the locus for the occurrence of domestic violence against women and femicide. Final considerations: It identifies the need to expand specific actions on the prevention of violence against women and femicide, as well as verifying the need to strengthen the assistance networks for women who have been raped, all of the above strategies are valid and complement each other.